Optimum Route Selection & Modified Network Approach to optimize Power aware Routing in MANET (International Journal of Engineering and Computer Science, 2017)
Energy consumption is a significant issue in ad hoc networks since mobile nodes are battery powered. In order  to  prolong  the  lifetime  of  ad  hoc  networks,  it  is  the  most  critical  issue  to  optimize  the  energy consumption  of  nodes.  In this paper, we propose a power aware routing protocol for choosing energy efficient optimum route selection & network approach. This system also considers transmission power of nodes and residual energy as  energy  metrics  in  order  to  maximize  the  network lifetime  and  to  reduce  energy  consumption  of  mobile nodes. The objective of our proposed system is to find an optimal route based on two energy metrics while choosing a route to transfer data packets. This system is implemented by using NS-2.35. Simulation results show  that  the  proposed  routing  protocol E-EPAR  with  transmission  power  and  residual  energy  control  mode  can extend the life-span of network and can achieve higher performance when compared to EPAR and DSR routing protocols.